Aktivitas Antimitosis dan Identifikasi Golongan Senyawa Aktif Ekstrak Daun Katuk (Sauropus androgynus L. Merr) terhadap Sel Telur Bulu Babi (Tripneustes gratilla Linn.) - Doloking, Haeria; Ningsi, Surya; Nasrawati Basir (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract Introduction: Katuk leaves (Sauropus androgynus L.Merr) are a plant that contains a variety of phytochemicals that have the potential to be developed as cancer drugs derived from natural ingredients. Objective: to determine the antimitotic activity of soluble and insoluble ethanol extracts of n-hexane of katuk leaves towards inhibiting cell division. sea urchin (Tripneustus gratilla Linn) eggs and determined the IC50 value of the n-hexane soluble and insoluble fractions, as well as identifying bioactive compounds in the most active Sauropus androgynus fraction. Methods: extraction using 96% ethanol solvent then partitioning using n-hexane solvent using liquid-solid technique. The extract obtained was then tested for its antimitotic effect using sea urchin egg cells. Results: The hexane insoluble extract had antimitotic activity with an IC50 of 0.79 μg/ml and the n-hexane soluble ethanol extract 16.46 μg/ml. Fractionation of the n-hexane insoluble ethanol extract using vacuum liquid chromatography produced 15 fractions which were further divided into subfractions A, B and C. Each subfraction had an IC50 of 2.63 μg/ml, 0.06 μg/ml and 3.98 μg/ml respectively. Conclusion: Fraction B showed the best activity with an inhibition value of 0.06 μg/ml. The results of the identification of bioactive compounds in fraction B showed the presence of phenol, flavonoid, triterpenoid, and steroid compounds. Keywords: cytotoxic, flavonoids, terpenoids, anti-cancer, subfraction